Learnings from Technological Interventions in a Low Resource Language: A Case-Study on Gondi - Mehta, Devansh; Santy, Sebastin; Mothilal, Ramaravind Kommiya; Srivastava, Brij Mohan Lal; Sharma, Alok; Shukla, Anurag; Prasad, Vishnu; U, Venkanna; Sharma, Amit; Bali, Kalika (Language Resources and Evaluation Conference (LREC), 2020)
The primary obstacle to developing technologies for low-resource languages is the lack of usable data. In this paper, we report the adaption and deployment of 4 technology-driven methods of data collection for Gondi, a low-resource vulnerable language spoken by around 2.3 million tribal people in south and central India. In the process of data collection, we also help in its revival by expanding access to information in Gondi through the creation of linguistic resources that can be used by the community, such as a dictionary, children’s stories, an app with Gondi content from multiple sources and an Interactive Voice Response (IVR) based mass awareness platform. At the end of these interventions, we collected a little less than 12,000 translated words and/or sentences and identified more than 650 community members whose help can be solicited for future translation efforts. The larger goal of the project is collecting enough data in Gondi to build and deploy viable language technologies like machine translation and speech to text systems that can help take the language onto the internet.